Analisis SWOT Perencanaan Pembelajaran Luring Di Madrasah Pada Masa Pandemi Corona Virus - Imam Sibaweh (Oasis : Jurnal Ilmiah Kajian Islam, 2023)
Planning is an activity process that are expected to minimize problems that arise so that an activity can achieve the goals that have been set. Analysis of Strengths, Weaknesses, Opportunities, and Threats or SWOT in planning learning in education is carried out for measuring the success of learning programs in schools through lesson plans and syllabi which are used as guidelines in implementing learning. This article aims to find out the results of the SWOT analysis of offline learning planning carried out at Asy-Syuhada Junior High School during the Covid-19 pandemic. The data obtained through the search for literature studies in various references to add the discussion in the article. The references used are the results of surveys, observations and interviews. The research method in this article is a descriptive qualitative research method that describes the occurrence of a learning process in an inclusive education setting. From this study, it can be concluded that the results of the SWOT analysis as the main strength factor for learning planning are the availability of adequate facilities for the continuity of the teaching and learning process. The weakness of schools in learning planning is that the preparation of lesson plans and syllabus by subject teachers is not in accordance with the conditions during the Covid-19 pandemic. Opportunities for schools to monitor students more effectively in the implementation of learning because school activity teaching and learning activities are carried out in the boarding school environment, besides that teachers who are not busy in school activity teaching and learning activities are a threat to schools because there will be outside activities so that there is a decrease in teacher loyalty to schools.Keywords           : Lesson Planning, New Normal, Covid-19. AbstrakPerencanaan adalah sebuah proses kegiatan yang disipakan dan disertai dengan berbagai langkah yang diharapkan dapat meminimalisir persoalan yang timbul agar sebuah kegiatan tersebut dapat mencapai tujuan yang telah ditetapkan. Analisis Strenghts, Weaknesses, Opportunities, dan Threats atau SWOT pada perencanaan pembelajaran dalam pendidikan merupakan cara mengukur keberhasilan program pembelajaran di sekolah melalui RPP dan silabus yang dijadikan pedoman dalam pelaksanaan pembelajaran. Artikel ini bertujuan untuk mengetahui hasil analisis SWOT perencanaan pembelajaran luring yang dilakukan di SMP Asy-Syuhada pada masa pandemi Covid-19.Data yang diperoleh melalui pencarian studi literatur di berbagai referensi untuk menambah pembahasan didalamartikel. Referensi yang digunakan adalah hasil survei, observasi dan wawancara. Metode penelitian dalam artikel ini adalah metode penelitian kualitatif deskriptif yang menggambarkan tentang kejadian suatu proses pembelajaran dalam setting pendidikan inklusif. Dari penelitian ini dapat disimpulkan bahwa hasil analisis SWOT sebagai faktor kekuatan utama perencanaan pembelajaran adalah tersedianya fasilitas yang memadai dalam keberlangsungan proses KBM. Sedangkan kelemahan sekolah dalam perencanaan pembelajaran adalah penyusunan RPP dan silabus oleh guru mata pelajaran belum sesuai dengan kondisi pada masa pandemi Covid-19. Peluang bagi sekolah dalam memantau siswa lebih efektif dalam pelaksanaan pembelajaran karena kegiatan KBM dilaksanakan didalam lingkungan pesantren, terlepas dari ini guru-guru yang tidak disibukkan dalam aktivitas KBM menjadi ancaman bagi sekolah karena akan mempunyai aktivitas diluar sehingga terjadi penurunan loyalitas guru kepada sekolah.Kata kunci: PerencanaanPembelajaran, New Normal, Covid-19.